Konservasi Ekoleksikon Pada Tradisi Mekare-Kare - Ni Putu Meira Purnama Yanti (Warmadewa Press, 2021)
The procession of implementing the mekare-kare tradition consists of nyikat, ngastiti, sabetan pandan, mecane, meboreh, and megibung. In carrying out each of these processions, the community uses several traditional tools and wears distinctive traditional clothes. The naming of each entity in this tradition represents the lexicon of flora and fauna and the formation of relationships between language, humans and the environment. This activity is carried out to conserve the ecolexicon on Mekare-kare tradition. The method used to collect data is to refer to the note-taking technique. The results showed that ecolexic treasures such as traditional swing, white thread, boreh curry, baas, balai patemu kelod, don pandan madui, gantih nyoman, gedong patemu, woven pegringsingan, kamen, nyikat, ngastiti, mecane, maboreh, magibung, saput, tamiang, tuak, tiing, and udeng. This ecolexicon is in the form of root words, affix words, and compound words which are categorized as nouns and verbs. In terms of meaning, this ecolexicon contains both lexical and cultural meanings. Then, the ideological dimension refers to the use of Balinese and several terms with certain concepts in the mekare-kare tradition by every member of the Tenganan Traditional Village community. The sociological dimension refers to the community interacting and communicating using the Balinese dialect of Tenganan in a series of implementation of the mekare-kare tradition. Meanwhile, the biological dimension can be seen from every community in the Traditional Village of Tenganan who utilizes the potential of flora (plants) and some abiotic elements to make the facilities used in the mekare-kare tradition.